Determination of the level of spontaneous chromosome abnormalities of the children with juvenile rheumatoid arthritis - Медзяновська, О. В. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2013)
The examination of the children with juvenile rheumatoid arthritis has been carried out and the level of spontaneous chromosome abnormalities has been defined. It has been shown that abnormalities are present in the cells of children with juvenile rheumatoid arthritis (the study group) and in the cells of healthy children (the control group). But the children with rheumatoid arthritis have the higher level (up to 1.8 times) comparing with the healthy peers (4.66% and 2.55% respectively, p<0.001). The range of chromosome abnormalities was wider among the children of the study group. In our investigation there were no differences in chromosome abnormalities depending on a sex and a form of the disease. Division into subgroups (depending on the rheumatoid arthritis continuance) showed the growth of the level of chromosome instability of the probands with continuation of the disease less than 3 years (5.04%) comparing with continuation more than 3 years (3.2%, p<0.01).